A Sociocultural Perspective: Human Conflict with Jaguars and Pumas in Costa Rica - Jennifer Rebecca Kelly (Conservation & Society, 2019)
This paper presents data about the sociocultural construction of conflict and the killing of jaguars and pumas in a part of the Mesoamerican Biological Corridor (MBC) of Costa Rica. Results from participant observation and 131 interviews revealed cultural differences between Ticos (non-Indigenous people) and Cabécar (Indigenous people) on four separate dimensions of conflict, where large felines were constructed as competitors, food, man-eaters, real and imagined. When compared to Ticos, Cabécar had more conflict, most likely because they live off the land and have frequent “real” encounters with felines. This study makes several contributions: 1) evidence suggests competition is not the only reason for killing large felines; motivations also include constructing them as man-eaters and as food, raising questions about the important role social and cultural factors play in solutions to conflict; 2) meanings from Cabécar are products of a traditional and modernised relationship with large felines; 3) Cabécar include jaguars as food, suggesting future research and conservation management must understand Indigenous Peoples' relations with large predators, including their diets and traditions; 4) potential for conflict may increase between Ticos and large felines as they repopulate; 5) culture is crucial to examine prior to management implementation.